2019
DOI: 10.3892/mmr.2019.10628
|View full text |Cite
|
Sign up to set email alerts
|

hNTCP‑expressing primary pig hepatocytes are a valuable tool for investigating hepatitis B virus infection and antiviral drugs

Abstract: Primary human hepatocytes (PHHs) are the ‘gold standard’ for investigating hepatitis B virus (HBV) infection and antiviral drugs. However, poor availability, variation between batches and ethical issues regarding PHHs limit their applications. The discovery of human sodium taurocholate co-transporting polypeptide (hNTCP) as a functional HBV receptor has enabled the development of a surrogate model to supplement the use of PHHs. In the present study, the evolutionary distance of seven species was assessed based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Based on the evolutionary distance, pigs and macaque were chosen. Macaque hepatocytes [11,19] and primary pig hepatocytes [11,18] expressing hNTCP exhibited increased expression levels of HBsAg and HBeAg, as well as increased cccDNA formation after HBV infection. Therefore we speculate that, the restriction of HBV infection is not only related to hNTCPdependent steps but also caused by lacking some additional species-speci c factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the evolutionary distance, pigs and macaque were chosen. Macaque hepatocytes [11,19] and primary pig hepatocytes [11,18] expressing hNTCP exhibited increased expression levels of HBsAg and HBeAg, as well as increased cccDNA formation after HBV infection. Therefore we speculate that, the restriction of HBV infection is not only related to hNTCPdependent steps but also caused by lacking some additional species-speci c factors.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the HBV receptor, hNTCP, led to the successful establishment of the cell line that susceptible for HBV and HDV. Zhou et al found that primary pig hepatocytes infected with hNTCP recombinant lentivirus were susceptible to HBV infection [18]. Burwitz et al showed macaque hepatocytes could support HBV replication in vitro following transduction with viral vectors encoding hNTCP, and increased amounts of HBV DNA in serum could also be detected over time in vivo [19].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evolutionary distance, pigs and macaque were chosen. Macaque hepatocytes (Burwitz et al 2017Lempp et al 2017) and primary pig (Lempp et al 2017Zhou et al 2019) hepatocytes expressing hNTCP exhibited increased expression levels of HBsAg and HBeAg, as well as increased cccDNA formation after HBV infection (Lempp et al 2016). Therefore we speculate that, the restriction of HBV infection is not only related to hNTCP-dependent steps but also caused by lacking some additional species-speci c factors.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the HBV receptor, hNTCP, led to the successful establishment of the cell line that susceptible for HBV and HDV. Zhou et al found that primary pig hepatocytes infected with hNTCP recombinant lentivirus were susceptible to HBV infection (Zhou et al 2019). Burwitz et al showed macaque hepatocytes could support HBV replication in vitro following transduction with viral vectors encoding hNTCP, and increased amounts of HBV DNA in serum could also be detected over time in vivo (Burwitz et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently its antitumor activities have attracted great interest of researchers. It has been demonstrated that LA inhibits the proliferation of different types of cancers, including gastric cancer BGC-823, AGS, SGC-7091 and MKN-45 cells, 12,13 bladder cancer T24 and 5367, 14 hepatocellular carcinoma HepG2 cells, 15 breast cancer MDA-MB-231 cells, 16 glioblastoma U87 cells, 17 nasopharyngeal carcinoma HONE-1, NPC-39 and NPC-BM cells, 18 cervical cancer SiHa and Hela cells, 19 osteosarcoma HOS and MG-63 cells, 20 lung cancer A549, H1299, H292 and H460, [21][22][23] and so on. In vivo studies also reveal that LA is a potent anticancer agent in gastric cancer, cervical cancer and colon cancer.…”
Section: Introductionmentioning
confidence: 99%